Concurrent cisplatin or cetuximab with radiotherapy for HPV-positive oropharyngeal cancer: Medical resource use, costs, and quality-adjusted survival from the De-ESCALaTE HPV trial. (January 2020) - Jones, David A.; Mistry, Pankaj; Dalby, Matthew; Fulton-Lieuw, Tessa; Kong, Anthony H.; Dunn, Janet; Mehanna, Hisham M.; Gray, Alastair M.
Abstract: Background: The De-ESCALaTE HPV trial confirmed the dominance of cisplatin over cetuximab for tumour control in patients with human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma (OPSCC). Here, we present the analysis of health-related quality of life (HRQoL), resource use, and health care costs in the trial, as well as complete 2-year survival and recurrence. Materials and methods: Resource use and HRQoL data were collected at intervals from the baseline to 24 months post treatment (PT). Health care costs were estimated using UK-based unit costs. Missing data were imputed. Differences in mean EQ-5D-5L utility index and adjusted cumulative quality-adjusted life years (QALYs) were compared using the Wilcoxon signed-rank test and linear regression, respectively. Mean resource usage and costs were compared through two-sample t-tests. Results: 334 patients were randomised to cisplatin (n = 166) or cetuximab (n = 168). Two-year overall survival (97·5% vs 90·0%, HR: 3.268 [95% CI 1·451 to 7·359], p = 0·0251) and recurrence rates (6·4% vs 16·0%, HR: 2·67 [1·38 to 5·15]; p = 0·0024) favoured cisplatin. No significant differences in EQ-5D-5L utility scores were detected at any time point. At 24 months PT, mean difference was 0·107 QALYs in favour of cisplatin (95% CI: 0·186 to 0·029, p = 0·007) driven by the mortality difference. Health care costs were similar across all categories except the procurement cost and delivery of the systemic agent, with cetuximab significantly more expensive than cisplatin (£7779 [P < 0.001]). Consequently, total costs at 24 months PT averaged £13517 (SE: £345) per patient for cisplatin and £21064 (SE: £400) for cetuximab (mean difference £7547 [95% CI: £6512 to £8582]). Conclusions: Cisplatin chemoradiotherapy provided more QALYs and was less costly than cetuximab bioradiotherapy, remaining standard of care for nonsurgical treatment of HPV-positive OPSCC. Highlights: Cisplatin was superior to cetuximab for tumour control. Quality-adjusted survival was significantly higher with cisplatin. Patients had similar medical resource utilisation in both arms. Cetuximab was more costly due to higher procurement cost. Chemoradiotherapy-related costs accounted for half of total per-patient costs.